Amelioration of testicular damages in renal ischemia/reperfusion by berberine: An experimental study - Gholampour, Firouzeh (Int J Reprod Biomed, 2019)
BACKGROUND: Ischemic acute kidney injury is associated with an inflammatory reaction. OBJECTIVE: In the current study, berberine was assessed for its effect on the functional disorders and histological damages of testis induced by renal ischemia/reperfusion (I/R). MATERIALS AND METHODS: Twenty-eight adult male Wistar rats (260-300 gr) were equally divided into four groups (n = 7/each): sham and I/R groups which received distilled water as well as berberine (BBR) and BBR + I/R groups which received berberine (15 mg/kg/day) orally seven days before the surgery. In both groups of sham and BBR, renal arteries were not clamped. Renal I/R was induced by occluding right and left renal artery for 45 min followed by a 24 hr reperfusion period. Blood samples were taken for determining the plasma levels of creatinine, urea nitrogen, FSH (follicle stimulating hormone), LH (luteinizing hormone), and testosterone. Then the rats were killed under deep anesthesia and the left testis was immediately isolated and preserved. RESULTS: The renal I/R injury led to testicular histological damages accompanied with increased plasma levels of creatinine, urea nitrogen, LH, and FSH, as well decrease of plasma testosterone concentration at the end of 24 hr reperfusion (All p [Formula: see text] 0.001, except for FSH p [Formula: see text] 0.01). Berberine diminished histological damage to the testis and attenuated the increase in plasma creatinine, urea nitrogen, LH, FSH, and decrease in plasma testosterone concentration in the BBR + I/R group (All p [Formula: see text] 0.001). CONCLUSION: These results suggest that ischemic acute renal failure induces functional disorders and tissue damages in testis of rat, which was improved through the administration of berberine.